2004
DOI: 10.1142/s0217979204025415
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Three-Group Evolutionary Minority Game

Abstract: Based on the adiabatic theory for the evolutionary minority game (EMG) that we proposed earlier[1], we perform a detail analysis of the EMG limited to three groups of agents. We derive a formula for the critical point of the transition from segregation (into opposing groups) to clustering (towards cautious behaviors). Particular to the three-group EMG, the strategy switching in the "extreme" group does not occur at every losing step and is strongly intermittent. This leads to an correction to the critical valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In exploring the evolutionary dynamics of complex systems, a variety of game models have been introduced [18,19,20,21,22,23]. In modeling the evolutionary mechanism in financial systems, the minority game (MG) and its variant, the evolutionary minority game (EMG) [24,25,26,27,28,29], have become promising tools. In the financial markets, market impact, which measures an upward or a downward tendency of the prices subsequent to a trade buying or selling a given size, is a key factor for an agent to consider before he is ready for a shift in investment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In exploring the evolutionary dynamics of complex systems, a variety of game models have been introduced [18,19,20,21,22,23]. In modeling the evolutionary mechanism in financial systems, the minority game (MG) and its variant, the evolutionary minority game (EMG) [24,25,26,27,28,29], have become promising tools. In the financial markets, market impact, which measures an upward or a downward tendency of the prices subsequent to a trade buying or selling a given size, is a key factor for an agent to consider before he is ready for a shift in investment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…To have a deep understanding of the evolutionary dynamics in financial markets, some agent-based models have been introduced in modeling the strategic interactions between the investors [20,21,22]. Among them, the minority game (MG) provides us a simple yet effective way to model the evolution of stock prices [23,24,25,26]. In the MG, the evolutionary mechanism is determined by two main factors: the global information and the individual strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Hod and Nakar generalized this to an asymmetric payoff structure, where the penalty for losing is greater than the reward for winning, and found the emergence of clustering of cautious agents [4]. Chen et al [5,6] derived a general formalism to understand the dynamical mechanism for the transition from segregation to clustering. They found that the effective rate of evolution plays an important role in determining the resulting steady-state population distribution.…”
Section: Introductionmentioning
confidence: 99%